Not Just the Luck of the Draw? Exploring Competency of Counsel and Other Qualitative Factors in Federal Court Refugee Leave Determinations (2005-2010) - Liew, Jamie Chai Yun; Zambelli, Pia; Thériault, Pierre-André; Silcoff, Maureen (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2021)
Refugee claimants who have received a negative decision from the Immigration and Refugee Board sometimes seek judicial treview at the Federal Court in Canada. Previous statistical studies, in particular Sean Rehaag’s (2012) study, “The Luck of the Draw,” have reported that rejected refugee claimants seeking judicial review face low and inconsistent leave grant rates, with chances of success largely dependent on judge assignment. The present research looks beyond these quantitative findings to identify additional factors that may explain the troubling statistics. To this end, four researchers manually reviewed 50 leave applications submitted between 2005 and 2010 and included in Rehaag’s (2012) data set. The results of this qualitative analysis are disturbing: a significant number of rejected leave applications had been poorly prepared, and a number of facially strong cases were denied leave. These results suggest that leave grant rates could rise if the quality of legal representation were enhanced. They also indicate that rejected refugee claimants would benefit from clear and uniformly applied criteria for granting leave.